DETERMINANTS OF CLEAN AND HEALTHY LIVING BEHAVIOR (PHBS) ON FAMILY LATRINE OWNERSHIP IN RANTO SABUN VILLAGE, PANTE PURBA SETTLEMENT, SAMPOINIET SUB-DISTRICT, ACEH JAYA DISTRICT IN 2023/2024 - Azhar, Firman; Seni, Wildan; Sarnika, Winda (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2023)
As stewards of the Earth, humans have a responsibility to protect and manage the environment, creating clean and healthy conditions that support life. While the environment's influence on humans is largely passive, human impact on the environment is notably active, with the capacity to alter it significantly. This study focuses on Clean and Healthy Living Behavior (PHBS) in households, identifying ten key indicators: childbirth assisted by health professionals, exclusive breastfeeding, regular weighing of children under five, use of clean water, proper hand-washing practices, utilization of sanitary latrines, mosquito larvae eradication, daily consumption of fruits and vegetables, regular physical activity, and maintaining a smoke-free home environment. These indicators serve as crucial benchmarks for assessing and promoting environmental health at the household level. This study's findings on Clean and Healthy Living Behavior (PHBS) in households have significant implications for public health, environmental management, and community development. The identified indicators can guide policy-making, urban planning, and health education campaigns, potentially reducing healthcare costs and improving overall well-being. These insights contribute to our understanding of sustainable household practices and their impact on community health, opening avenues for future research and global health initiatives.